An improved first-mode-based pushover analytical procedure for assessing seismic performance of special moment resisting frame building structures. (1st February 2022) - Worku, Aman Mola; Hsiao, Po-Chien
Highlights: Proposed a modified first-mode-based pushover analysis procedure to assess the seismic performance of SMRF buildings. Clarify the features of the responses by the modal pushover analysis. Clarify the merits and demerits of the conventional nonlinear static procedures on estimating the dynamic responses of buildings. Improved and reasonable accuracy of the proposed pushover analysis procedures was verified compared to the existing ones. Abstract: With the aim of performance-based design of building structures, nonlinear response history analysis (NRHA) procedures are required to reliably obtain the realistic responses of the buildings which, however, involve much complex procedures and reduce the feasibility of the practical uses. Nonlinear static procedure (NSP) analysis conventionally solely based on the first-mode of the structure are typically adopted in the design practice for approximately assessing seismic performances. Modal pushover analysis (MPA) and other modified NSP procedures were developed to include the higher-mode-effects in the NSP analysis, while they are still not feasible for the general practical uses. The study proposed a relatively simple procedure, named the modified first-mode-based pushover analysis (MFPA), for accurately assessing various seismic performances of steel buildings under MCE-level events through a single-step pushover process with a novel load pattern until a target displacement. Against mathematical approaches, a wide range of model building cases, including five-, ten-, fifteen-, and twenty-story buildings of special moment resisting frames (SMRFs) with two types of story heights were designed and examined in the study to verify the validity of the MFPA procedures. The results verified that the proposed MFPA procedures enabled to consistently more accurately assess the peaks and distributions of the inter-story responses of buildings obtained by the NRHA compared to other NSP and MPA approaches, and form an alternative method for the practical applications.